Adaptation And Concept Of Indonesia Online Police Record Certificate (SKCK Online) In Realising Police Services In Society 5.0 - Alfin Reza Syahputra (Jurnal Manajemen Pelayanan Publik, 2024)
The Society 5.0 era has an impact on all sectors of life, including the Indonesian National Police. In line with one of the main tasks of the police, the efforts made are by providing a Police Record Certificate (SKCK). With the development of technology, this SKCK can be issued online. The purpose of this research is to explore the adaptation and concept of making an online Police Record Certificate (SKCK) in Indonesia in the context of Society 5.0. The research method used is a literature study. The literature study was used to describe relevant facts and information. According to the findings of this research, police record issuance services are still not optimally implementing online systems. Although some countries, such as Australia, have successfully implemented an online police record system. This research also highlights the importance of improving the Indonesia online police record certificate (SKCK online) system, strengthening the criminal and offence databases, designing a system that is easily accessible regardless of residence, socializing criminal records on SKCK, and using blockchain technology on online police record system. Therefore, this research recommendation emphasizes that SKCK Online services need to be improved with specific actions, features, and services. So that INP’s services become more effective in Society 5.0.